Perceived Benefits, Barriers, and Drivers of Telemedicine From the Perspective of Skilled Nursing Facility Administrative Staff Stakeholders. (January 2018) - Driessen, Julia; Castle, Nicholas G.; Handler, Steven M.
Potentially avoidable hospitalizations (PAHs) of skilled nursing facility (SNF) patients are common and costly. Telemedicine represents a unique approach to manage and potentially reduce PAHs in SNFs, having been used in a variety of settings to improve coordination of care and enhance access to providers. Nonetheless, broad implementation and use of telemedicine lags in SNFs relative to other health care settings. To understand why, we surveyed SNF administrative staff attending a 1-day telemedicine summit. Participants saw the highest value of telemedicine in improving the quality of care and reducing readmissions. They identified hospital and managed care telemedicine requirements as primary drivers of adoption. The most significant barrier to adoption was the initial investment required. A joint research-policy effort to improve the evidence base around telemedicine in SNFs and introduce incentives may improve adoption and continued use of telemedicine in this setting.